2012
DOI: 10.1099/jmm.0.035014-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunochromatic kits Xpect Legionella and BinaxNOW Legionella for detection of Legionella pneumophila urinary antigen have low sensitivities for the diagnosis of Legionnaires’ disease

Abstract: Urinary antigen tests are the most widely used methods for diagnosing Legionnaires' disease (LD). However, all available urinary antigen tests have the disadvantage that they have low or no sensitivity for serogroups (sgs) other than Legionella pneumophila sg 1. Recently, Oxoid introduced the Xpect Legionella test for detection of L. pneumophila sg 1 and sg 6. In this study, we have evaluated the Xpect kit together with the BinaxNOW kit and compared them with the Binax EIA kit. One hundred and fifteen urine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Further confirmation of serogroup was conducted with the Dresden panel of monoclonal antibodies [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Further confirmation of serogroup was conducted with the Dresden panel of monoclonal antibodies [23]. …”
Section: Methodsmentioning
confidence: 99%
“…13,14 Urine antigen testing is widely used for two organisms: S. pneumoniae , where the test performs well in adults; 15,16 and L. pneumophila , where the test is specific and much quicker than culture but lacks sensitivity, especially in less severe cases. 17 …”
Section: Introductionmentioning
confidence: 99%
“…The most widely used clinical diagnostic method for all suspected legionellosis cases are rapid, non-invasive, urine detection tests that recognize the presence of soluble antigen [36]. These clinical tests provide high sensitivity for Sg1 infection diagnosis but they are unable to detect most non-Sg1 strains [37], [38]. Recently, we reported that 34% of culture confirmed cases of legionellosis in Ontario (n = 351) were caused by non-Sg1 L. pneumophila species in the last 3 decades [39].…”
Section: Introductionmentioning
confidence: 99%